Status of geriatric education and meeting the standards of facilities in dental schools - Bahareh Tahani; Abbasali Khademi; Sadaf Fathollahi (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: Information, specific tendencies, and skills are needed to provide oral care for the elderly population, and these skills should be learned in dental schools. AIMS: The aim of the study was to assess the status of geriatric dentistry education and meeting the standards of facilities in dental schools in Iran. SETTINGS AND DESIGN: In this cross-sectional study, sampling was done by census method, and all the 18 dental schools with a history of ≥6 years of establishment were selected. MATERIALS AND METHODS: A checklist was prepared in two sections, including geriatric dentistry education (existence of specific education module, considered time, specific department, specific faculty members, continuing courses for dentists, relationship with geriatric nursing houses, referral system, and specific clinics) and facilities and was distributed among dental schools. The collected data were input into SPSS (Version 20.0. Armonk, NY: IBM Corp) and analyzed descriptively. RESULTS: After a regular follow-up, 11 dental schools returned the completed checklists. Eight (72%) of them had specific geriatric dentistry education module. Only one (9%) had specific faculty member, continuing educational course, mobile clinic, and regular connection with geriatric nursing houses. None of the dental schools had specific department, specific clinic for delivering care, and a referral system from hospitals to the schools. There were no dental schools with a special transportation system for the elderly and the staff to accompany the patients without attendants. CONCLUSION: The status of geriatric dental education in Iran seems not adequate. Furthermore, dental schools are not equipped with necessary facilities for delivering care to the elderly.